Alveolar ridge preservation in preparation for implant placement: Alveolar ridge preservation sebagai persiapan pemasangan implan - Arni Irawaty Djais; Laetitia Evangeline Ana Tukan (Makassar Dental Journal, 2024)
Alveolar bone resorption is inevitable after tooth extraction. Alveolar ridge preservation (ARP) is a procedure to preserve and minimise alveolar bone resorption after tooth extraction for future prosthodontic treatment including dental implant placement. A total of 25 references were collected through an internet-based search using keywords, five of which were closely related to the topic at hand, namely the relationship between ARP treatment in preparation for implant placement in the last ten years analy-sed through table synthesis. ARP is a procedure to preserve or minimise alveolar ridge resorption after tooth extraction. ARP procedures using graft materials such as autograft, allograft, xenograft, or alloplastic, have been shown to minimise alveolar bone resorption so that implants requiring an ideal ridge can be obtained. It is concluded that ARP can minimise alveolar bone resorption post extraction and optimise the ridge prior to implant placement.